Relationship between problem solving skills appraisal, perceived stress, hopelessness, hardiness, and suicidal ideation among undergraduate students in public universities in Selangor - Abdollahi, Abbas (2015)
Suicide is a serious and growing public health problem, and it remains a serious cause of death in the world. It is reported that young Malaysians in the 16 to 24 year age group has the highest prevalence of acute and chronic suicidal ideation compared to other age groups. In addition, recent evidence suggests that suicidal ideation is increasing among university students. This highlights the idea that university students are at-risk populations. Therefore, this study was designed to examine the relationships between problem-solving skills appraisal, perceived stress, hardiness,and hopelessness with suicidal ideation; the mediation roles of hopelessness and hardiness on problem-solving skills appraisal and perceived stress with suicidal ideation; and the moderating role of gender on the relationships between problemsolving skills appraisal, perceived stress, hopelessness, and hardiness with suicidal ideation among undergraduate students. The present study utilized the Shneidman theory of suicidal ideation, hardiness theory, and the diathesis stress-hopelessness theory in providing a valid basis for explaining and predicting suicidal ideation among undergraduate students. The multi-stage cluster random sampling method was employed to recruit a total of 500 undergraduate students aged 18 to 24 years from public universities in the Selangor state. Quantitative study using correlational research design was employed. The respondents completed the Problem-Solving Inventory (Heppner, 1988), Perceived Stress Scale (Cohen et al., 1983), Personal Views Survey (Maddi et al., 2006), Beck Hopelessness Scale (Beck et al., 1974), and the Beck Scale for Suicidal Ideation (Beck et al.,1988). Structural equation modeling indicated that undergraduate students with poor problem-solving skills, high perceived stress, high hopelessness, and low hardiness were more likely to report suicidal ideation. Hardiness and hopelessness partially mediated the relationships between problem-solving skills appraisal and perceived stress with suicidal ideation. Additionally, this study supported the moderating role of gender between hardiness and perceived stress with suicidal ideation. Hopelessness was the strongest predictor of suicidal ideation among undergraduate students. The findings of this study proposed that perceived stress, problem-solving skills appraisal, hopelessness, and hardiness were valuable predictors of suicidal ideation among undergraduate students. These variables explained 88.0% of the variance in suicidal ideation. The findings of this study showed that the obtained mean of suicidal ideation for Muslim students was lower than others. The current study advances understanding on the importance of problem-solving skills and hardiness as influencing factors against suicidal ideation. It also increases understanding on the importance of perceived stress and hopelessness as risk factors of suicidal ideation among undergraduate students. The findings of the current study can be useful for therapists, parents, university students, counsellors, and policy makers to prevent suicidal ideation.